The Changes of Leukocytes in Brain and Blood After Intracerebral Hemorrhage - Mei, Shuhao; Shao, Yijie; Fang, Yuanjian; Lu, Jia'nan; Zheng, Jingwei; Xu, Shenbin; Wu, Haijian; Sun, Zeyu; Yu, Jun; Chen, Sheng; Wang, Zhen; Zhang, Jianmin (Frontiers in Immunology, 2021)
Preclinical and clinical research has demonstrated that inflammation is a critical factor regulating intracerebral hemorrhage (ICH)-induced brain injury. Growing evidence suggests that myeloid cells and lymphocytes have an effect on the pathophysiological processes associated with ICH, such as inflammation, immune responses, perihematomal edema formation, blood–brain barrier (BBB) integrity, and cell death. However, the underlying mechanisms remain largely unknown. We aimed to explore the role immune cells played at different stages of the ICH. To achieve this, novel bioinformatics algorithms were employed to analyze the gene expression profiles and three different analytical tools were utilized to predict the abundances of cell types. In this study, we found that natural killer (NK) cells infiltrated into the brain parenchyma after ICH. Infiltrating NK cells may mediate brain injury through degranulation and recruitment of other cells. Besides, in the acute phase of ICH, monocytes in peripheral blood carried out phagocytosis and secretion of cytokines. On the other hand, in the subacute stage, non-classical monocytes were activated and showed a stronger ability to carry out heme metabolism, wound healing, and antigen processing and presentation. In conclusion, our findings emphasize the significance of intracerebral infiltrating immunocytes in ICH and demonstrate that ICH is a systemic disease affected by peripheral blood. The hub genes identified might be promising therapeutic targets. We also provide a reference on how to use bioinformatics approaches to explore non-neoplastic immune-related diseases.